Aesop's fables (Janetta Otter-Barry books, 2011)
Here are 16 of Aesop's wise, witty and timeless fables, portrayed for the first time in an African setting. This is an exciting new interpretation of one of the world's great classics. This unique story collection is vividly illustrated by Beverley Naidoo's fellow South African Piet Grobler, an internationally acclaimed illustrator